How can planning for sustainability improve Costa de Caparica's nightlife? - Almeida, Diana (2019)
In the twentieth century, several transformations occurred in the way society used and perceived urban lighting. This allowed the growth of leisure and other activities related to free time and culture into the night period. Night gained an increasing importance among urban policies and therefore required to be framed within these complex urban contexts as well as other planning processes. This article addresses the Polis Program and its contribution to the improvement of Costa de Caparica’s nightlife. It aims to analyse the urban renewal intervention of the Polis Program at Costa de Caparica in terms of night economy and sustainability concerns, in light of Egan’s sustainable communities’ components. The argument is that the planning of night can contribute to the construction of a sustainable community. The main conclusions focus on the importance that should have been given to governance, public participation and equity components of Egan’s wheel along the implementation of the programme, as well as in planning processes broadly, towards achieving a sustainable nightlife.